Multibeam bathymetry raw data (EM 120 echosounder entire dataset) of RV MARIA S. MERIAN during cruise MSM10/3 - Dubilier, Nicole; Borowski, Christian (PANGAEA, 2025)
Multibeam bathymetry raw data using the ship's own Kongsberg (Simrad) EM 120 multibeam echosounder was almost continuously recorded during RV MARIA S. MERIAN cruise MSM10/3. Data was recorded on 31 days between 2009-01-12 and 2009-02-12. This dataset contains a transit survey in the North Atlantic Ocean and a survey covering the Fifteen-Twenty fracture zone close to the Mid-Atlantic Ridge. The approximate average depth of the entire dataset is around 4700m. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. No ancillary sound velocity profiles (SVP) files from the cruise are archived at the BSH, thus no SVP files are added to this dataset. However, data analysis of the multibeam raw data revealed that SVP has been changed at one occasion during the survey. This publication is conducted within the efforts of the German Marine Research Alliance in the core area 'Data management and Digitalization' (Deutsche Allianz Meeresforschung, DAM). Data are unprocessed and therefore contains incorrect depth measurements (artifacts) without further processing. Note that refraction errors can be expected due to the lack of proper SVP. Overall, it appears that the data quality is rather good during the survey at the Fifteen-Twenty fracture zone since the gridded hillshade data showed relatively few obstacles. However, during the transit survey the data coverage is not always fully covering the seafloor (gaps in the data). The reason for this is unknown. Data can be processed e.g. with the open source software package MB-System (Caress et al. 2024, https://doi.org/10.5281/zenodo.6302801).
Keywords: Bathymetry; Multibeam Echosounder